2009
DOI: 10.1007/s10522-009-9259-6
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent cognitive impairment in a Drosophila Fragile X model and its pharmacological rescue

Abstract: Fragile X syndrome afflicts 1 in 2,500 individuals and is the leading heritable cause of mental retardation worldwide. The overriding clinical manifestation of this disease is mild to severe cognitive impairment. Age-dependent cognitive decline has been identified in Fragile X patients, although it has not been fully characterized nor examined in animal models. A Drosophila model of this disease has been shown to display phenotypes bearing similarity to Fragile X symptoms. Most notably, we previously identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 58 publications
3
64
0
Order By: Relevance
“…Lithium treatment, which modulates signaling in a manner similar to mGluR antagonists, also increased naive courtship and restored short-term memory in FXS flies (McBride et al, 2005). A later study further found that treatment with mGluR antagonists or lithium effectively prevented age-related cognitive impairments in this Drosophila model of FXS (Choi et al, 2010).…”
Section: F Fxsmentioning
confidence: 86%
“…Lithium treatment, which modulates signaling in a manner similar to mGluR antagonists, also increased naive courtship and restored short-term memory in FXS flies (McBride et al, 2005). A later study further found that treatment with mGluR antagonists or lithium effectively prevented age-related cognitive impairments in this Drosophila model of FXS (Choi et al, 2010).…”
Section: F Fxsmentioning
confidence: 86%
“…The following strategies were confirmed in studies using Drosophila models of fragile X syndrome (FXS): metabotropic glutamate receptor (mGluR) [167], gamma-aminobutyric acid (GABA) [168] (but see [169]), lithium [167], minocycline [170], phosphodiesterase-4 (PDE-4) [ A recent study suggested that simultaneous stimulation of D1R and serotonin (5HT) receptors rescued impaired synaptic AMPA receptor insertion and plasticity, and improved fear conditioning and Y maze learning deficits [115]. § Simultaneous inhibition of mGlu5 and CB1R was additive in this study.…”
Section: Macro-orchidismmentioning
confidence: 99%
“…Therefore, social interactions such as naïve courtship were studied in aged dFmr1 mutant flies, but no further differences were reported in comparison to young flies (Choi et al 2010). Additional studies using dFmr1 transgenic flies expressing only proteins with mutations in the KH domains (I244N or I307N) revealed reduced naïve courtship activity, suggesting that this effect is likely due to the lack of dFMRP's ability to bind a specific subset of mRNAs (Banerjee et al 2007).…”
Section: Dfmr1 Mutant Flies Show Impairment In Social Interactionmentioning
confidence: 99%